Початок розслідування умисних вбивств або заподіяння тяжких тілесних ушкоджень у разі перевищення меж необхідної оборони чи перевищення заходів, необхідних для затримання злочинця - Гузєй, В. М.; Huziei, V. M. (Вісник Харківського національного університету внутрішніх справ. - 2014. - № 4 (67). - С. 45-51, 2014)
Встановлено особливості початку розслідування умисних убивств або заподіяння тяжких тілесних ушкоджень у разі перевищення меж необхідної оборони чи перевищення заходів, необхідних для затримання злочинця. На основі аналізу кримінальних проваджень обґрунтовано необхідність попередньої перевірки повідомлень про вчинення вказаних злочинів.

The article is devoted to determination of features of initial stage of the investigation of murders or cause of grievous bodily harm in case of defense measures’ excess or exceeding the measures necessary to apprehend a criminal, because of the adoption of the new Criminal Procedure Code of Ukraine there have been significant changes not only in the conceptual system but also in the stages of the criminal process. These changes are particularly topical in the context of procedural order of the initial stage of criminal proceedings. The author of the paper supports the thesis that the criminal procedural activities of an investigator begin before entering information about the crime commission into the Unified register of pre-trial investigations. The author proves the need to verify the information about commission of such acts for pre-qualification. Based on the analysis of the investigative and judicial practice, as well as specialized literature the author notes the circumstances that can and should be set at the initial stage of the investigation of murders or cause of grievous bodily harm in case of defense measures’ excess or exceeding the measures necessary to apprehend a criminal. Optimal actions of an investigator to achieve the goals and fulfill the tasks of the initial stage of the investigation are determined.

Установлены особенности начала расследования убийств или причинения тяжких телесных повреждений в случае превышения мер необходимой обороны или превышения мер, необходимых для задержания преступника. На основе анализа уголовных производств обоснована необходимость предварительной проверки сообщений о совершении указанных преступлений.
Initiation of the investigation of murders or cause of grievous bodily harm in case of defense measures’ excess or exceeding the measures necessary to apprehend a criminal
Начало расследования умышленных убийств или причинения тяжких телесных повреждений в случае превышения мер необходимой обороны или превышения мер, необходимых для задержания преступника
Гузєй, В. М. Початок розслідування умисних вбивств або заподіяння тяжких тілесних ушкоджень у разі перевищення меж необхідної оборони чи перевищення заходів, необхідних для затримання злочинця / В. М. Гузєй // Вісник Харківського національного університету внутрішніх справ. - 2014. - № 4 (67). - С. 45-51.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; вбивство; тілесні ушкодження; перевищення меж необхідної оборони; перевірка повідомлень про злочин; початок розслідування; murder; bodily injury; excess of necessary self-defense measures; checking reports about crimes; beginning of the investigation; убийство; телесные повреждения; превышение мер необходимой обороны; проверка сообщений о преступлениях; начало расследования